2021
DOI: 10.1016/j.heliyon.2021.e07543
|View full text |Cite
|
Sign up to set email alerts
|

The use of YouTube in developing the speaking skills of Jordanian EFL university students

Abstract: This study examines the effectiveness of using YouTube videos in teaching the speaking skills among English as a Foreign Language (EFL) students in Jordan. The study sample comprised 80 students attending Oral Skills classes in the English Language and Literature Department at a private university in Jordan. The participants were equally divided into a control group and an experimental group of 40 students each. The experimental group was taught through the use of YouTube videos, while the control group was ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
56
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 20 publications
(33 reference statements)
14
56
0
2
Order By: Relevance
“…YouTube is a good site to be used in enhancing students' listening comprehension. It was discovered that YouTube supply both visual and audio to the learners which gave the students the opportunity to figure out the speech or words that they heard while learning the subject content as well as improving their language ability (Saed et al, 2021;Selvi et al, 2020). The study result shows that students' motivation and participation can be enhancing when using YouTube as authentic materials.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…YouTube is a good site to be used in enhancing students' listening comprehension. It was discovered that YouTube supply both visual and audio to the learners which gave the students the opportunity to figure out the speech or words that they heard while learning the subject content as well as improving their language ability (Saed et al, 2021;Selvi et al, 2020). The study result shows that students' motivation and participation can be enhancing when using YouTube as authentic materials.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, YouTube videos give the students chance to memorize the lesson more easily. Some previous researcher also had been examined the effect of using YouTube video in teaching listening skill (Ho & Tai, 2020;Saed et al, 2021). The result of the research showed that there was a positive effect of using YouTube video in improving students' listening ability.…”
Section: Introductionmentioning
confidence: 99%
“…For the students, online learning with various materials and strategies makes the EFL teaching and learning process interesting [63]. In terms of the students' achievement on language skills and language elements, some studies also confirmed that the use of online learning could help the students to improve their competence in those language skills and elements [64]- [67]. However, technology is merely a tool that helps the teachers deliver the instruction.…”
Section: Technology In Efl Online Learningmentioning
confidence: 99%
“…Studies have observed that the use of technology in English language teaching (ELT) fosters autonomous learning and decreases students' anxiety about the learning process. Many researchers have explored the use of social media platforms in ELT, such as Twitter (Upadhyay & Upadhyay, 2020), Instagram (Wulandari, 2019), YouTube channel (Saed et al, 2021;Sari, 2017), Facebook group (Ab Manan, 2012;Mabuan & Ebron, 2016;Ong et al, 2020). All these studies have concluded that incorporating the use of social media in ELT is able to promote autonomous learning among ESL learners.…”
Section: The Use Of Social Media Platforms In Eltmentioning
confidence: 99%